2020
DOI: 10.3390/cryst10070587
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Crystal Structure, and Fungicidal Activity of Two Fenclorim Derivatives

Abstract: Two fenclorim derivatives (compounds 6 and 7) were synthesized by linking active sub-structures using fenclorim as the lead compound. The chemical structures of the two compounds were confirmed by NMR spectroscopy, high resolution mass spectrometry, and X-ray diffraction analysis. Their fungicidal activity against six plant fungal strains was tested. Compounds 6 and 7 both crystallized in the monoclinic system, with a P21/c space group (a = 8.4842(6) Å, b = 24.457(2) Å, c = 8.9940(6) Å, V = 1855.0(2) Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
0
3
0
Order By: Relevance
“… 40 , 41 We previously evaluated the fungicide activity of fenclorim and proved it could be used as a fungicide-lead compound as this compound showed certain fungicide activity toward fungi such as Sclerotinia sclerotiorum , Fusarium oxysporum , Fusarium graminearum , and Thanatephorus cucumeris . 42 , 43 However, to the best of our knowledge, only a few reports have so far described the SAR of fungicidal activities of fenclorim or its analogues, indicating that more studies are needed. 44 Besides, it should be noted that these research studies revealed that strategic structural modifications of the chemical skeleton of fenclorim at the position of chlorine atom on the pyrimidine ring can yield novel molecules with new interesting properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 , 41 We previously evaluated the fungicide activity of fenclorim and proved it could be used as a fungicide-lead compound as this compound showed certain fungicide activity toward fungi such as Sclerotinia sclerotiorum , Fusarium oxysporum , Fusarium graminearum , and Thanatephorus cucumeris . 42 , 43 However, to the best of our knowledge, only a few reports have so far described the SAR of fungicidal activities of fenclorim or its analogues, indicating that more studies are needed. 44 Besides, it should be noted that these research studies revealed that strategic structural modifications of the chemical skeleton of fenclorim at the position of chlorine atom on the pyrimidine ring can yield novel molecules with new interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among all commercial herbicide safeners, fenclorim (4,6-dichloro-2-phenyl-pyrimidine) is a pyrimidine-type herbicide safener used for chloroacetanilide herbicides. , When fenclorim is soaked with rice seeds in pre-sowing applications or combination with chloroacetanilide herbicides on rice seedlings, it improves the tolerance of rice seedlings to chloroacetanilide herbicides. Fenclorim detoxifies herbicides by improving the GST expression, catalyzing the conjugation of chloroacetanilide herbicides with glutathione in rice. , We previously evaluated the fungicide activity of fenclorim and proved it could be used as a fungicide-lead compound as this compound showed certain fungicide activity toward fungi such as Sclerotinia sclerotiorum, Fusarium oxysporum, Fusarium graminearum, and Thanatephorus cucumeris. , However, to the best of our knowledge, only a few reports have so far described the SAR of fungicidal activities of fenclorim or its analogues, indicating that more studies are needed . Besides, it should be noted that these research studies revealed that strategic structural modifications of the chemical skeleton of fenclorim at the position of chlorine atom on the pyrimidine ring can yield novel molecules with new interesting properties…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic utility of this system was further demonstrated by the synthesis of fluorinated fenclorim analogues (Scheme a), which are used to protect wet-sown rice from pretilachlor . Standard reaction conditions were readily scaled to 1 mmol, yielding the corresponding product 5i in 62% yield.…”
mentioning
confidence: 99%